LOCAL WISDOM IN SOUTH SULAWESI’S FOLKLORES - Salmia Syarifuddin; Irmawaty Hasyim; Firmansyah Firmansyah (Universitas Negeri Surabaya, 2022)
Local wisdom commonly refers to as local intelligence. This term is the idea or thought of the local community in which local wisdom as values of hereditary nobility followed by Society. Local wisdom reflects the cultural community of South Sulawesi. South Sulawesi local story spread around Society orally and is often referred to as oral folklore. These folklores have local wisdom. The people of South Sulawesi are a compound community consisting of various tribes and with diversity. These tribes have different local wisdom and, until now, are still held firmly. Even so, these tribes have similarities in terms of local wisdom inscribed in the oral folklores. This research aims to describe the local wisdom found in the oral folklore owned by South Sulawesi Community. This research aims to describe the local wisdom found in the oral folklore owned by South Sulawesi Community. This research used the qualitative method. It applied descriptive analysis by applying observation, interview, and content analysis. The folklores used in this study as the data were oral folklores. Three (3) oral folklores were chosen as the data in this study. They were pemmali for the pregnant woman sitting close to the door, mole on the palm, and pemmali for cleaning or sweeping the house floor at night. The study's results showed local wisdom in oral folklore existed in South Sulawesi society. These oral folklores are full of wisdom and values embedded in the pattern of people's lives in South Sulawesi. Besides, the local wisdom found in the oral folklore is still maintained today. The three oral folklores found and discussed represent the regions and tribes in South Sulawesi.